Discovery of rifampicin as a new anti-glycating compound by matrix-assisted laser desorption/ionization mass spectrometry-based insulin glycation assay - Golegaonkar, Sandeep B.; Bhonsle, Hemangi S.; Boppana, Ramanamurthy; Kulkarni, Mahesh J. (European Journal of Mass Spectrometry, 2010)
An in vitro insulin glycation assay was developed for screening glycation inhibitors. The assay involves the use of matrix-assisted laser desorption/ionization time-of-flight mass spectrometry for monitoring the formation of glycated insulin. The assay is simple, rapid and amenable for high throughput screening. Using this assay we have discovered a strong anti-glycation activity for the anti-tuberculosis drug rifampicin. These results were compared with bovine serum albumin glucose fluorescence assay. In addition, the IC(50) of rifampicin was lower than that of aminoguanidine, a known anti-glycating agent, suggesting that rifampicin is a more potent glycation inhibitor.
Keywords: AGE; aminoguanidine; antibiotic; diabetic complication; drug repositioning; IC(50)

Dynamic proteome in enigmatic preeclampsia: an account of molecular mechanisms and biomarker discovery - Mary, Sheon; Patil, Gouri V.; Kulkarni, Asmita V.; Kulkarni, Mahesh J.; Joshi, Sadhana R.; Mehendale, Savita S.; Giri, Ashok P. (Proteomics Clinical Applications, 2012)
The coevolution of genomics and proteomics has led to advancements in the field of diagnosis and molecular mechanisms of disease. Proteomics is now stepping into the field of obstetrics, where early diagnosis of pregnancy complication such as preeclampsia (PE) is imperative. PE is a multifactorial disease characterized by hypertension with proteinuria, which is a leading cause of maternal and neonatal morbidity and mortality occurring in 5-7% of pregnancies worldwide. This review discusses the probable molecular mechanisms that lead to PE and summarizes the proteomics research carried out in understanding the pathogenicity of PE, and for identifying the candidate biomarker for diagnosis of the disease.
Keywords: Hypertension; Oxidative stress; Pregnancy complication; Proteinuria

Development of diagnostic fragment ion library for glycated peptides of human serum albumin: targeted quantification in prediabetic, diabetic, and microalbuminuria plasma by parallel reaction monitoring, SWATH, and MSE - Korwar, Arvind M.; Vannuruswamy, Garikapati; Jagadeeshaprasad, Mashanipalya G.; Jayaramaiah, Ramesha H.; Bhat, Shweta; Regin, Bhaskaran S.; Ramaswamy, Sureshkumar; Giri, Ashok P.; Mohan, Viswanathan; Balasubramanyam, Muthuswamy; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2015)
Human serum albumin is one of the most abundant plasma proteins that readily undergoes glycation, thus glycated albumin has been suggested as an additional marker for monitoring glycemic status. Hitherto, only Amadori-modified peptides of albumin were quantified. In this study, we report the construction of fragment ion library for Amadori-modified lysine (AML), N(epsilon)-(carboxymethyl) lysine (CML)-, and N(epsilon)-(carboxyethyl) lysine (CEL)-modified peptides of the corresponding synthetically modified albumin using high resolution accurate mass spectrometry (HR/AM). The glycated peptides were manually inspected and validated for their modification. Further, the fragment ion library was used for quantification of glycated peptides of albumin in the context of diabetes. Targeted Sequential Window Acquisition of all THeoretical Mass Spectra (SWATH) analysis in pooled plasma samples of control, prediabetes, diabetes, and microalbuminuria, has led to identification and quantification of 13 glycated peptides comprised of four AML, seven CML, and two CEL modifications, representing nine lysine sites of albumin. Five lysine sites namely K549, K438, K490, K88, and K375, were observed to be highly sensitive for glycation modification as their respective m/z showed maximum fold change and had both AML and CML modifications. Thus, peptides involving these lysine sites could be potential novel markers to assess the degree of glycation in diabetes.

Dietary flaxseed oil and fish oil ameliorates renal oxidative stress, protein glycation, and inflammation in streptozotocin-nicotinamide-induced diabetic rats - Jangale, Nivedita M.; Devarshi, Prasad P.; Bansode, Sneha B.; Kulkarni, Mahesh J.; Harsulkar, Abhay M. (Journal of Physiology and Biochemistry, 2016)
Protective and prophylactic effects of omega-3 fatty acids on oxidative stress and inflammation are well known. We assessed beneficial effects of flaxseed oil and fish oil on streptozotocin (65 mg/kg; i.p.)-nicotinamide (110 mg/kg; i.p.) induced diabetic rats by studying renal expression of antioxidant and inflammatory genes. Diabetic rats given 10 % flaxseed oil or 10 % fish oil diet for 35 days showed significant decrease in renal lipid peroxidation. Flaxseed oil diet resulted in up-regulation of renal superoxide dismutase-1 (SOD-1) (activity and expression) and glutathione peroxidase-1 (GPx-1) expression. Furthermore, both diets up-regulated catalase (CAT) (activity and expression) and down-regulated heme oxygenase-1 (HO-1) expression. Both diets were able to limit the renal advanced glycation end products (AGEs) formation and reduced receptor of AGE (RAGE) protein expression significantly. Expressions of interleukin-6 (IL-6) and NF-kappa B p65 subunit were down-regulated significantly by flaxseed oil or fish oil diet. The histological tubular injuries were also lowered by both diets. These results suggest that dietary omega-3 fatty acids may slow the progression of diabetic nephropathy (DN) associated with oxidative stress, glycation, and inflammation in the kidney.
Keywords: Diabetes; Fish oil; Flaxseed oil; Glycation; Kidney; Streptozotocin

Differential accumulation of vimentin fragments in preeclamptic placenta - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Cytoskeleton, 2017)
Preeclampsia is a pregnancy complication that is the result of abnormal placentation because of inadequate trophoblast invasion into spiral arteries that prevent normal blood flow to the placenta. We report the alteration in vimentin protein proteolysis in placenta of normotensive and preeclamptic women, which is known to have a role in many physiological functions other than its major function in the structural integrity of the cell. Placental proteome from normotensive (n=25) and preeclamptic pregnancies (n=25) showed eight differentially accumulated protein spots of vimentin (proteolytic fragments) by two-dimensional electrophoresis. Immunoblots of normotensive and preeclamptic placenta revealed a difference in proteolytic processing of vimentin. In particular, lower molecular weight vimentin fragments of 32 and 20 kDa were 3.3 and 2.6-fold (p<0.0001) higher, respectively, in preeclampsia compared with normotensive placenta.

Development of multiple reaction monitoring assay for quantification of carnosine in human plasma - Pandya, Vaibhav Kumar; Sonwane, Babasaheb; Rathore, Rajeshwari; Unnikrishnan, A. G.; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (RSC Advances, 2020)
Carnosine, a histidine containing dipeptide, exerts beneficial effects by scavenging reactive carbonyl compounds (RCCs) that are implicated in pathogenesis of diabetes. However, the reduced carnosine levels may aggravate the severity of diabetes. The precise quantification of carnosine levels may serve as an indicator of pathophysiological state of diabetes. Therefore, we have developed a highly sensitive targeted multiple reaction monitoring (MRM) method for quantification of carnosine in human plasma samples. Various mass spectrometry parameters such as ionization of precursor, fragment abundance and stability, collision energy, tube lens offset voltage were optimized to develop a sensitive and robust assay. Using the optimized MRM assay, the lower limit of detection (LOD) and limit of quantification (LOQ) for carnosine were found to be 0.4 nM and 1.0 nM respectively. Standard curves were constructed ranging from 1.0 nM to 15.0 mu M and the levels of carnosine in mice and human plasma were determined. Further, the MRM assay was extended to study carnosine hydrolyzing activity of human carnosinases, the serum carnosinase (CN1) and the cytosolic carnosinase (CN2). CN1 showed three folds higher activity than CN2. The MRM assay developed in this study is highly sensitive and can be used for basal plasma carnosine quantification, which can be developed as a novel marker for scavenging of RCCs in diabetes.

Discovery of potential multi-target-directed ligands by targeting host-specific SARS-CoV-2 structurally conserved main protease - Joshi, Rakesh S.; Jagdale, Shounak S.; Bansode, Sneha B.; Shankar, S. Shiva; Tellis, Meenakshi B.; Pandya, Vaibhav Kumar; Chugh, Anita; Giri, Ashok P.; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has resulted in the current COVID-19 pandemic. Worldwide this disease has infected over 2.5 million individuals with a mortality rate ranging from 5 to 10%. There are several efforts going on in the drug discovery to control the SARS-CoV-2 viral infection. The main protease (M-Pro) plays a critical role in viral replication and maturation, thus can serve as the primary drug target. To understand the structural evolution of M-Pro, we have performed phylogenetic and Sequence Similarity Network analysis, that depicted divergence of Coronaviridae M-Pro in five clusters specific to viral hosts. This clustering was corroborated with the comparison of M-Pro structures. Furthermore, it has been observed that backbone and binding site conformations are conserved despite variation in some of the residues. These attributes can be exploited to repurpose available viral protease inhibitors against SARS-CoV-2 M-Pro. In agreement with this, we performed screening of similar to 7100 molecules including active ingredients present in the Ayurvedic anti-tussive medicines, anti-viral phytochemicals and synthetic anti-virals against SARS-CoV-2 M-Pro as the primary target. We identified several natural molecules like delta-viniferin, myricitrin, taiwanhomoflavone A, lactucopicrin 15-oxalate, nympholide A, afzelin, biorobin, hesperidin and phyllaemblicin B that strongly binds to SARS-CoV-2 M-Pro. Intrestingly, these molecules also showed strong binding with other potential targets of SARS-CoV-2 infection like viral receptor human angiotensin-converting enzyme 2 (hACE-2) and RNA dependent RNA polymerase (RdRp). We anticipate that our approach for identification of multi-target-directed ligand will provide new avenues for drug discovery against SARS-CoV-2 infection. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; COVID-19; hACE-2; MPro; multi-target-directed ligand; protease inhibitor; RdRp; SARS-CoV-2 virus

De novo structure prediction of meteorin and meteorin-like protein for identification of domains, functional receptor binding regions, and their high-risk missense variants - Shankar, S. Shiva; Banarjee, Reema; Jathar, Swaraj M.; Rajesh, S.; Ramasamy, Sureshkumar; Kulkarni, Mahesh J. (Journal of Biomolecular Structure & Dynamics, 2024)
Meteorin (Metrn) and Meteorin-like (Metrnl) are homologous secreted proteins involved in neural development and metabolic regulation. In this study, we have performed de novo structure prediction and analysis of both Metrn and Metrnl using Alphafold2 (AF2) and RoseTTAfold (RF). Based on the domain and structural homology analysis of the predicted structures, we have identified that these proteins are composed of two functional domains, a CUB domain and an NTR domain, connected by a hinge/loop region. We have identified the receptor binding regions of Metrn and Metrnl using the machine-learning tools ScanNet and Masif. These were further validated by docking Metrnl with its reported KIT receptor, thus establishing the role of each domain in the receptor interaction. Also, we have studied the effect of non-synonymous SNPs on the structure and function of these proteins using an array of bioinformatics tools and selected 16 missense variants in Metrn and 10 in Metrnl that can affect the protein stability. This is the first study to comprehensively characterize the functional domains of Metrn and Metrnl at their structural level and identify the functional domains, and protein binding regions. This study also highlights the interaction mechanism of the KIT receptor and Metrnl. The predicted deleterious SNPs will allow further understanding of the role of these variants in modulating the plasma levels of these proteins in disease conditions such as diabetes.
Keywords: domains; Meteorin; meteorin-like; missense variants; protein-protein interactions; structure prediction

Discovery of free glycated amines and glycated urea in diabetic plasma: potential implications in diabetes - Shaikh, Rashdajabeen Q.; Das, Sancharini; Chaurasiya, Arvindkumar; Ashtamy, Murali G.; Sheikh, Amreen B.; Fernandes, Moneesha; Tiwari, Shalbha; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (ACS Omega, 2024)
The role of protein glycation in the pathogenesis of diabetes has been well established. Akin to proteins, free amino acids and other small-molecule amines are also susceptible to glycation in hyperglycemic conditions and may have a role in the pathogenesis of the disease. However, information about glycation of free amino acids and other small-molecule amines is relatively obscure. In the quest to discover small-molecule glycated amines in the plasma, we have synthesized glycated amino acids, glycated creatine, and glycated urea, and by using a high-resolution accurate mass spectrometer, a mass spectral library was developed comprising the precursor and predominant fragment masses of glycated amines. Using this information, we report the discovery of the glycation of free lysine, arginine, and leucine/isoleucine from the plasma of diabetic patients. This has great physiological significance as glycation of these amino acids may create their deficiency and affect vital physiological processes such as protein synthesis, cell signaling, and insulin secretion. Also, these glycated amino acids could serve as potential markers of diabetes and its complications. While other amines, such as creatinine and urea, accumulate in the plasma and act as biomarkers of diabetic nephropathy. For the first time, we report the detection of glycated urea in diabetic plasma, which is confirmed by matching the precursor and fragment masses with the in vitro synthesized glycated urea by using C-12(6) and C-13(6)-glucose. Further, we quantified glycated urea detected in two forms, monoglycated urea (MGU) and diglycated urea (DGU), by a targeted mass spectrometric approach in the plasma of healthy, diabetic, and diabetic nephropathy subjects. Both MGU and DGU showed a positive correlation with clinical parameters, such as blood glucose and HbA1c. Given that urea gets converted to glycated urea in hyperglycemic conditions, it is crucial to quantify MGU and DGU along with the urea for the diagnosis of diabetic nephropathy and study their physiological role in diabetes.

Dual modification of tau by pseudophosphorylation and glycation does not enhance amorphous aggregation - Chinnathambi, Subashchandrabose; Sonawane, Shweta Kishor; Chandrashekar, Madhura; Chidambaram, Hariharakrishnan; Thulasiram, Shrivatsa; Kulkarni, Mahesh J. (Cellular Physiology and Biochemistry, 2024)
<h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Background/Aims: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The neurofibrillary tangles consisting of Tau protein are an important pathology in Alzheimer’s disease. The paired helical filaments of Tau form most of the NFTs. These PHFs of Tau are found to carry numerous post-translational modifications, which stabilize them and aid in aggregation. The mechanistic function of Tau is to bind and stabilize the axonal microtubules. Hyperphosphorylation of Tau causes it to compromise its physiological function and accumulate in the neurons in the form of aggregates. Such residue-specific phosphorylation has been studied by employing Tau pseudophosphorylation mutants. But in addition to phosphorylation, several other modifications also aid in stabilizing the Tau PHF. Glycation is one such non-enzymatic PTM caused by sugars and their reactive intermediates. In this study, we employed the pseudophosphorylated Tau double mutants (262/404D, 262/396D, and 231/262) for studying their modification by methyl glyoxal, a reactive intermediate of glucose metabolism.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Methods: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> We studied various biophysical properties like aggregation propensity, Advanced glycation end-product formation, and global conformation of the Tau with dual modifications. Our study includes the use of <i style="box-sizing: border-box; color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">in vitro <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;">techniques e.g., ThS fluorescence assay, electron microscopy, CD spectroscopy, SDS-PAGE.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Results: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> The overall result of the study suggest that the MG-induced Tau aggregation is influenced by the residue-specific Tau phosphorylation.  <h1 class="article-paragraph" style="box-sizing: border-box; margin-top: 30px; margin-bottom: 10px; line-height: 20px; color: rgb(33, 37, 41); font-size: 14px; text-align: justify; font-style: italic; display: inline; font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji";"> Conclusion: <span style="color: rgb(33, 37, 41); font-family: system-ui, -apple-system, "Segoe UI", Roboto, "Helvetica Neue", "Noto Sans", "Liberation Sans", Arial, sans-serif, "Apple Color Emoji", "Segoe UI Emoji", "Segoe UI Symbol", "Noto Color Emoji"; font-size: 14px; text-align: justify;"> In conclusion, the combinatorial effect of discreet PTMs on Tau function could lead to a better understanding of Tauopathy.